2021
DOI: 10.1002/ppul.25273
|View full text |Cite
|
Sign up to set email alerts
|

Tracheostomy trends in preterm infants with bronchopulmonary dysplasia in the United States: 2008–2017

Abstract: Objective To determine the trends in tracheostomy placement and resource use in preterm infants less than or equal to 30 weeks gestational age (GA) with bronchopulmonary dysplasia (BPD) in the United States from 2008 to 2017. Study design This was a retrospective, serial cross‐sectional study using data from the NIS. Inclusion criteria were: GA less than or equal to 30 weeks, hospitalization at less than or equal to 28 days of age, assignment of International Classification of Diseases, Ninth Revision, Clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 44 publications
1
13
0
2
Order By: Relevance
“…Prolonged mechanical ventilation in post-prematurity infants with severe bronchopulmonary dysplasia (BPD) is now the most common indication for tracheostomy in infants ( 5 , 6 ). As advanced technology in neonatal intensive care units (NICUs) becomes more routine, the survival of extremely premature infants has also increased the need for long-term mechanical ventilation ( 7 ), specifically for those infants born at the threshold of viability (≤24 weeks' gestation), who have greater odds of developing severe BPD ( 8 , 9 ). Other reasons for performing tracheostomy in infants include congenital anomalies of the airway, neurological and complex cardiac anomalies, and genetic diseases with either short- or long-term survival outcome ( 7 , 8 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolonged mechanical ventilation in post-prematurity infants with severe bronchopulmonary dysplasia (BPD) is now the most common indication for tracheostomy in infants ( 5 , 6 ). As advanced technology in neonatal intensive care units (NICUs) becomes more routine, the survival of extremely premature infants has also increased the need for long-term mechanical ventilation ( 7 ), specifically for those infants born at the threshold of viability (≤24 weeks' gestation), who have greater odds of developing severe BPD ( 8 , 9 ). Other reasons for performing tracheostomy in infants include congenital anomalies of the airway, neurological and complex cardiac anomalies, and genetic diseases with either short- or long-term survival outcome ( 7 , 8 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found that the rate of tracheostomy in infants increased from 1.9 to 3.5 per 100,000 live births between 2011 and 2017 with a corresponding increase in hospital costs ( 8 ). Murthy et al reported that among members of the Children's Hospital Neonatal Consortium (CHNC), the incidence of tracheostomy varied between centers ranging from as low as 2% to as high as 37%, showing that the indication of tracheostomy in severe BPD infants remains uncertain ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, in vitro data on antifibrotics have not only demonstrated an ability to slow down the initiation and progression of lung fibrosis, including the release of proinflammatory and profibrotic mediators, but also to inhibit the vascular cell proliferation. 59 With the recent approval of antifibrotic medications for fibrosing ILDs such as IPF and SSc-ILD, we may potentially see a decrease in the incidence of PH-ILD and PAH in the future.…”
Section: Ild-specif Ic Treatment: Antif Ibrotics and Immunosuppressionmentioning
confidence: 99%
“…These infants are overall a small proportion of total BPD patients, but they are a high-risk population with high morbidity and mortality, requires specialized care, and has grown in recent years. 59 An interdisciplinary team including neonatology, otolaryngology, pulmonology, respiratory therapy, and palliative care may be helpful in determining which patients would benefit from tracheostomy placement and best determine the timing for this intervention.…”
Section: Tracheostomymentioning
confidence: 99%